2013
DOI: 10.1371/journal.pone.0078053
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating Predictive Pharmacogenetic Signatures of Adverse Events in Colorectal Cancer Patients Treated with Fluoropyrimidines

Abstract: The potential clinical utility of genetic markers associated with response to fluoropyrimidine treatment in colorectal cancer patients remains controversial despite extensive study. Our aim was to test the clinical validity of both novel and previously identified markers of adverse events in a broad clinical setting. We have conducted an observational pharmacogenetic study of early adverse events in a cohort study of 254 colorectal cancer patients treated with 5-fluorouracil or capecitabine. Sixteen variants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 45 publications
(40 reference statements)
3
40
1
Order By: Relevance
“…CDA 79A>C has been associated with CDA activity and with toxicity to cytarabine, which is also metabolized by CDA [31, 32]. In contrast to our findings, those of other studies did not show a connection between this SNP and toxicity induced by capecitabine [11, 22] and fluoropyrimidines [33]. The variables considered responsible for these discrepant results include differences in study design, sample size, criteria for establishing a cut-off for severe ADRs, as well as variations in concomitant medication [34].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…CDA 79A>C has been associated with CDA activity and with toxicity to cytarabine, which is also metabolized by CDA [31, 32]. In contrast to our findings, those of other studies did not show a connection between this SNP and toxicity induced by capecitabine [11, 22] and fluoropyrimidines [33]. The variables considered responsible for these discrepant results include differences in study design, sample size, criteria for establishing a cut-off for severe ADRs, as well as variations in concomitant medication [34].…”
Section: Discussioncontrasting
confidence: 99%
“…Afzal et al used polymorphisms in TYMS and MTHFR to predict gastrointestinal toxicity in 5-FU-treated patients [19], while Rosmarin et al developed a test to predict overall toxicity with polymorphisms in TYMS and DPYD in capecitabine-treated patients [11]. Jennings et al suggested a predictive test for early adverse events by analyzing TYMP and DPYD variants as a signature (sensitivity of 45.5% and a positive predictive value of 39.9%) [33]. Our results for predicting overall toxicity using the CDA-ABCB1 score are similar to those obtained in the studies, although they do not take into consideration the main factor contributing to toxicity in fluoropyrimidine-based treatments, namely, DPYD variants.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study identified a deep intronic variant (c.1129-5923 C>G; rs75017182) in tight linkage with HapB3 that was shown to affect pre-mRNA splicing [12]. Though evidence suggests a correlation between c.1129-5923 C>G / hapB3 and severe 5-FU toxicity [13,14], other studies have shown no significant associations [6, 15-17]. …”
mentioning
confidence: 99%
“…Up to date, 160 single nucleotide polymorphisms (SNPs) that alter the DPD aminoacids sequence have been identified within the gene (DPYD) codifying for this enzyme 5,6 and many clinical studies have been trying to investigate their association with FL-related severe toxicities. 3,[7][8][9][10][11] Recently the discussion in the scientific community about the clinical effectiveness of pharmacogenetics has given rise to the publication of drug dosing guidelines with indications and recommendations about drug-related genetic tests and …”
mentioning
confidence: 99%
“…Up to date, 160 single nucleotide polymorphisms (SNPs) that alter the DPD aminoacids sequence have been identified within the gene (DPYD) codifying for this enzyme 5,6 and many clinical studies have been trying to investigate their association with FL-related severe toxicities. 3,[7][8][9][10][11] Recently the discussion in the scientific community about the clinical effectiveness of pharmacogenetics has given rise to the publication of drug dosing guidelines with indications and recommendations about drug-related genetic tests and their integration in the clinical routine. In particular, the Clinical Pharmacogenetics Implementation Consortium (CPIC) 12,13 and the Dutch Pharmacogenetics Working Group of the Royal Dutch Association for the Advancement of Pharmacy (DPWG) 14 have published drug-specific guidelines based on the patient genotype.…”
mentioning
confidence: 99%